2021
DOI: 10.1056/nejmoa2103784
|View full text |Cite
|
Sign up to set email alerts
|

Early Convalescent Plasma for High-Risk Outpatients with Covid-19

Abstract: Background Early administration of convalescent plasma obtained from blood donors who have recovered from coronavirus disease 2019 (Covid-19) may prevent disease progression in acutely ill, high-risk patients with Covid-19. Methods In this randomized, multicenter, single-blind trial, we assigned patients who were being treated in an emergency department for Covid-19 symptoms to receive either one unit of convalescent plasma with a high titer of antibodies against severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
225
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(239 citation statements)
references
References 12 publications
6
225
1
Order By: Relevance
“…CCP therapy requires matching on blood type, ordering the CCP, which may or may not be available on site, and setting up the transfusion. This inherent delay from randomization to infusion means that RCTs may build in a disadvantage for the CCP study arm, where controls may have received treatment earlier in the disease course (as, for example, in the CP3O trial (23). ABO-compatible CCP units may be not readily available at the local blood bank and recruited patients may have to wait for a compatible unit of CCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCP therapy requires matching on blood type, ordering the CCP, which may or may not be available on site, and setting up the transfusion. This inherent delay from randomization to infusion means that RCTs may build in a disadvantage for the CCP study arm, where controls may have received treatment earlier in the disease course (as, for example, in the CP3O trial (23). ABO-compatible CCP units may be not readily available at the local blood bank and recruited patients may have to wait for a compatible unit of CCP.…”
Section: Resultsmentioning
confidence: 99%
“…This finding has implication for RCTs that use nationally sourced (centralized) CCP, since the attempt to standardize the therapeutic units centrally could inadvertently reduce CCP efficacy if hospitals use CCP obtained from distant loci. For example, in the C3PO RCT, which was conducted in 21 USA states, 95% of the donor CCP was collected in either Chicago or Denver: since only 4 of the 48 centers were in Illinois or Colorado, most CCP usage had to be from remote sources (23). By contrast, the NCT04359810 RCT in New York and Brazil used CCP locally sourced in New York, whose efficacy against P.1 was tested to ensure efficacy at the other recruiting center in Brazil (11).…”
Section: Resultsmentioning
confidence: 99%
“…However, based on further findings from observational studies, the beneficial effects of CCP were limited to units with high titers of neutralizing antibodies (nAbs) administered early after infection, and efficacy was not confirmed by recent large randomized trials 3 . For example, the Clinical Trial of COVID-19 Convalescent Plasma in Outpatients (C3PO) study showed no significant beneficial effect in mildly symptomatic treated patients compared to controls 4 , with similar findings in the CONCOR-1 study in hospitalized patients 5 ; both were halted early for futility.…”
Section: Introductionmentioning
confidence: 82%
“…These studies suggested that CP acts like a conventional antiviral, so benefit may be seen only when CP is administered early in the disease course with donor units containing potent, high-titer antibodies. Disappointingly, however, the C3PO (Convalescent Plasma in Outpatients With COVID-19) trial (ClinicalTrials.gov: NCT04355767) in recently diagnosed outpatients failed to show benefit ( 23 ).…”
Section: Convalescent Plasmamentioning
confidence: 99%